Pulsed cathodoluminescence of WS2 nanocrystals at various electron excitation energy densities: Defect induced sub-band gap emission - Bozheev F. E. Farabi Esimovich; Valiev D. T. Damir Talgatovich; An V. V. Vladimir Vilorievich; Nemkaeva R. R. Renata Ruslanovna; Tikhonov A. V. Aleksandr Valerjevich; Sagurbekova G. A. Gulnara Akimovna (2017, 2017)
Title screen